Development of an Approach to Integrated Epidemiological Zoning of West Nile Fever Endemic Territory (by the Example of the Volgograd Region) - D. N. Nikitin; S. K. Udovichenko; K V Zhukov; E. V. Putintseva; D. V. Viktorov; A. V. Toporkov (Эпидемиология и вакцинопрофилактика)
Relevance. The widespread occurrence of West Nile fever (WNF) in the Russian Federation and the various intensity of epidemic process manifestations determine the relevance of developing a methodology for epidemiological zoning and differentiation of the country's territory by the level of potential epidemic hazard, which will optimize WNF pathogen monitoring and a set of preventive measures. Aims. To develop a methodology for differentiating the territory according to the degree of potential epidemic hazard of West Nile virus (WNV) infection and to test it by the example of the Volgograd region. Materials & Methods. The work used: information on the detection of WNF cases in the Volgograd region in 1999–2019, the results of serological and entomological monitoring for the 1999–2020 period, meteorological data (air temperatures in June-August, 1999–2020), vector maps of hydrography and land use. Results and discussion. As criteria for assessing the potential epidemic hazard of the territory, the following have determined: the number of patients, the number of years of case registration, the average air temperature during WNV transmission season, the identification of markers (antigens/RNA) of the pathogen in environmental objects (carriers, vectors, marker species of animals), the number of the main pathogen's vectors, positive results of serological screening of the population, as well as the level of organization of the epidemiological surveillance system and the level of preparedness of health authorities and institutions for the identification, diagnosis and treatment of patients with WNF. On the basis of the methodology developed by us using the spatial cluster analysis and the method of scoring indicators, an epidemiological zoning of the Volgograd region has carried out in terms of the WNV infection risk. As a result, more than 50% of the territory belongs to the zones of increased risk due to the combined action of biotic, abiotic and social factors. Conclusions. The results obtained indicate the need for targeted monitoring of the pathogen in the territories of the Volgograd region with unconfirmed WNV circulation (northeastern and northwestern regions). In the future, application the developed methodology in practice when carrying out zoning of WNV-endemic territories of the Russian Federation is planned, primarily the subjects of the Southern Federal District, which are characterized by the most intense course of the epidemic process.